The efficacy of percutaneous treatment methods in bile duct stones - Güngören, Fatma Zeynep; Erol, Cengiz; Şeker, Mehmet; Güzelburç, Vahit; Akgül, Erol (Springer, 2023)
We aimed to search for the efficacy of percutaneous transhepatic cholangiography-guided balloon sphincteroplasty, mechanical lithotripsy, and laser lithotripsy in the treatment of bile duct stones and share our experience in retrievable internal plastic biliary stents derived from drainage catheter. Twenty-nine patients, in whom endoscopic retrograde cholangiopancreatography was contraindicated or failed, were included in this retrospective study. Balloon sphincteroplasty and balloons were used as the first choice of percutaneous treatment for stone removal. In four patients (14%), combined treatment with balloon sphincteroplasty and laser lithotripsy was performed. Plastic internal biliary stent converted from drainage catheter was advanced in 14 patients (48%). In 18 (62%) patients, a single procedure was performed while two sessions were required for nine patients and three sessions for two patients. Complete stone removal was achieved in 86% of the patients, and small residual stones remained in the biliary duct in four patients (14%). Two patients (7%) had minor complications including pain and fever, and the symptoms were ameliorated with conservative management. Stent retromigration was encountered in one patient (3.4%). The median follow-up time of the study was 4 months (range 1-51 months). Percutaneous treatment choices in bile duct stones are low-cost and safe methods that can be used efficiently if indicated.
Keywords: Balloon Sphincteroplasty; Bile Duct Stones; Internal Plastic Biliary Stent; Mechanical Lithotripsy; Percutaneous Treatment